Cholestatic Jaundice in Nursing Practice, Clinical Laboratory Diagnostics, and General Internal Medicine: Assessment, Evaluation, and Multidisciplinary Management - Al Eid, Fatma Abdulaziz; Hind Hassan Ali Homadi,; Khadijah Ali Ali Awaji,; Maram Ali Ali Awaji,; Saad Mohammed Eid Al Modara,; Nalahma Maghram Ahmed Aseri,; Wadyah Ahmed Mohammed Yahya,; Jameel Ahmed Mohammed Majrashi,; Sameer Ali Ibrahim Zakri,; Faisal Ali Ali Mujarrbi,; Fahad Ali Ali Sharahili, (Saudi Journal of Medicine and Public Health, 2025)
Background: Cholestatic jaundice results from impaired bile formation or flow, leading to systemic retention of bilirubin and bile acids. It may arise from intrahepatic dysfunction or extrahepatic obstruction, each producing characteristic clinical, biochemical, and histopathological patterns. Its diverse etiologies—ranging from metabolic, infectious, inflammatory, obstructive, genetic, and drug induced disorders—necessitate comprehensive diagnostic evaluation. Aim: To review the mechanisms, clinical presentation, diagnostic approach, and multidisciplinary management of cholestatic jaundice, emphasizing differentiation between intrahepatic and extrahepatic causes. Methods: This review synthesizes pathophysiological concepts, epidemiology, histopathology, and clinical assessment, integrating laboratory, imaging, and biopsy based diagnostic strategies. Management approaches for both obstructive and hepatocellular cholestasis are examined, alongside therapeutic options for complications such as pruritus. Results: Cholestatic jaundice presents with jaundice, pruritus, fat soluble vitamin deficiency, and biochemical patterns dominated by conjugated hyperbilirubinemia and elevated alkaline phosphatase. Ultrasonography and MRCP are central to distinguishing obstructive from non obstructive etiologies. Management of extrahepatic obstruction relies on biliary decompression through ERCP, stenting, or surgery, while hepatocellular cholestasis requires treatment of underlying causes and symptom directed therapy. Refractory pruritus may require second line pharmacologic or procedural interventions. Conclusion: Cholestatic jaundice is a multifactorial clinical syndrome requiring early recognition, structured diagnostic assessment, and coordinated multidisciplinary management. Timely intervention reduces hepatic injury, prevents complications, and improves patient outcomes.